Urgensi Kompetensi Pribadi Bagi Calon Konselor dalam Mewujudkan Pelayanan yang Prima - Muwakhidah Muwakhidah; Hartono Hartono; Ryandika Firmasyah; Nur Syamsiah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
Abstract: Implementationally, the role of counselors in practice guidance and counseling services in schools is actually inseparable from the problem of competence counselor. Counselor's competency issues refer to the ability of the counselor, particularly the personal competence of the counselor. Problems concerning true personal competence are not only experienced by counselors, but student college also experience such a thing. The process of implementing counseling that seems "rushed," lies in techniques that seem to run "stiff", prioritizing quantity over quality that results in "sterility" of the counseling process, and a series of "flat" activities without an underlying assist role, Is the impact of the low personal competence of student college. The low of personal competence has an impact on the quality of counseling and guidance services. This article describes the importance of personal competence for student college in realizing professional services. Abstrak: Secara implementasi, peran konselor dalam praktik layanan bimbingan dan konseling di sekolah sebenarnya tidak terlepas dari masalah kompetensi konselor. Masalah kompetensi konselor mengacu pada kemampuan konselor, khususnya kompetensi personal konselor. Permasalahan mengenai kompetensi diri yang sebenarnya tidak hanya dialami oleh para konselor, tetapi mahasiswa juga mengalami hal yang demikian. Proses pelaksanaan konseling yang terkesan “terburu-buru”, terletak pada teknik yang terkesan berjalan “kaku”, mengutamakan kuantitas daripada kualitas yang mengakibatkan proses konseling menjadi “steril”, dan rangkaian kegiatan yang “datar” tanpa peran pendamping yang mendasarinya. Apakah dampak dari rendahnya kompetensi kepribadian mahasiswa perguruan tinggi. Rendahnya kompetensi personal berdampak pada kualitas layanan bimbingan dan konseling. Artikel ini menjelaskan pentingnya kompetensi personal bagi mahasiswa perguruan tinggi dalam mewujudkan pelayanan profesional.